The Role of Discursive Behavior in the Colombian Conflict - Milan Školník (Vojenské rozhledy, 2020)
One of the longest conflicts in Latin-American history ended in 2016 when then Colombian President Juan Manuel Santos signed a peace agreement with the Revolutionary Armed Forces of Colombia (FARC), the largest guerrilla movement in Colombia. His predecessor, the current senator Álvaro Uribe, opposed the peace agreement, believing that an offensive against the guerrillas was the right approach. This article shows how these two Colombian presidents framed guerillas and what strategies and expressions were used in their presidential speeches. The main argument is that the conciliatory discourse of President Santos helped to finally achieve peace. The research paper uses a comparative method and the concept of framing.